Ratio of lymphocyte to monocyte area under the curve as a novel predictive factor for severe infection in multiple sclerosis - Takahashi, Junichiro; Okamoto, Tomoko; Lin, Youwei; Saika, Reiko; Katsumoto, Atsuko; Sato, Wakiro; Yamamura, Takashi; Takahashi, Yuji (Frontiers in Immunology, 2023)
Background: Individuals with multiple sclerosis (MS) are vulnerable to all types of infection. Simple predictive variables for infection that are easily assessed in daily examinations are warranted. Lymphocyte area under the curve (L_AUC), defined as the sum of serial absolute lymphocyte counts under the lymphocyte count-time curve, has been established as a predictive factor for several infections after allogenic hematopoietic stem cell transplantation. We assessed whether L_AUC could also be a useful factor for predicting severe infection in MS patients. Methods: From October 2010 to January 2022, MS patients were retrospectively reviewed. We extracted patients with infection requiring hospitalization (IRH) from medical records and matched with controls in a 1:2 ratio. Variables including clinical severity and laboratory data were compared between the infection group and controls. L_AUC was calculated along with the AUC of neutrophils (N_AUC), and monocytes (M_AUC). Further, we defined the ratio of [L_AUC] to [follow-up duration] as [L_AUC/t] to correct for different times of blood examination and extract mean values of AUC per time point. Multivariate regression analysis was conducted to extract predictive factors associated with IRH. Also, discriminative analysis was conducted using candidate variables from multivariate analysis. Results: The total case-control sample included 177 patients of MS with IRH (n=59) and non-IRH (controls) (n=118). Adjusted odds ratios (OR) for IRH in patients with MS with higher baseline expanded disability status scale (EDSS) (OR 1.340, 95% confidence interval [CI] 1.070–1.670, p = 0.010) and lower ratio of L_AUC/t to M_AUC/t (OR 0.766, 95%CI 0.591–0.993, p = 0.046) were significant. In discriminative analysis, sensitivity was 88.1% and specificity was 35.6% , using EDSS ≥ 6.0 or ratio of L_AUC/t to M_AUC/t ≤ 3.699, while sensitivity was 55.9% and specificity was 83.9% , using both EDSS ≥ 6.0 and ratio of L_AUC/t to M_AUC/t ≤ 3.699. Conclusion: Our study revealed the impact of the ratio L_AUC/t to M_AUC/t as a novel prognostic factor for IRH. Clinicians should pay more attention to laboratory data such as lymphocyte or monocyte counts itself, directly presenting individual immunodeficiency, rather than the kind of drug to prevent infection as a clinical manifestation.